The influence of demography, travel history and comorbidity toward the mortality incidence due to Covid-19 in Semarang - Wulandari, Rita Laila; Purnami, Cahya Tri; Agushybana, Farid; Mawarni, Atik (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Semarang is one of the cities in Central Java with the highest positive number and mortality rate of Covid-19. It became the largest contributor to daily cases in Central Java. In general, the severity of Covid-19 in Semarang is 5.3% and increased to 24% in the elderly. Mortality Covid-19 was caused by various factors such as demographic and non-demographic factors. Objective: This study aims to determine the impact of several risk factors of COVID-19 mortality in Semarang. Methods: This is an analytical cross-sectional study. Data analysis was carried out analytically with a binary logistic regression test. The sample used was the total population of 32.555 confirmed positive from March 2020 to March 2021 registered in Semarang Health Office. Results: The results demonstrated that mortality due to Covid-19 in Semarang was frequent in the elderly (27.3%), males (9.4%), had comorbidities such as diabetes mellitus (28.6%), kidney disease (43.5%), neuromuscular (36.4%), and cancer (29.3%), and accompanied by symptoms such as Dyspnea (18.1%), weakness/lethargy (19.9%), and fever (14.6%). Conclusion: Age, gender, travel history, comorbidities (kidney, neuromuscular, cancer, and diabetes mellitus), and symptoms (fever, shortness of breath, and weakness/lethargy) are risk factors for mortality Covid-19 in Semarang.